Comparando as idades à primeira relação sexual, à primeira união e ao nascimento do primeiro filho de duas coortes de mulheres brancas e negras em Belo Horizonte: evidências quantitativas Comparing the ages at first intercourse, first union and first childbirth of two cohorts of write and mixed-race females in Belo Horizonte, Brazil: quantitative indications - Andréa Branco Simão; Paula Miranda-Ribeiro; André Junqueira Caetano; Cibele Comini César (Revista Brasileira de Estudos de População, 2006)
Este trabalho apresenta um estudo sobre as idades à primeira relação sexual, ao primeiro casamento e ao nascimento do primeiro filho de mulheres brancas e negras, de 20 a 29 anos e 50 a 59 anos, em Belo Horizonte. Os objetivos centrais são: verificar as mudanças ocorridas nas idades à primeira relação sexual, ao primeiro casamento e ao nascimento do primeiro filho; e analisar se as diferenças constatadas são mais evidentes quando se considera a coorte de nascimento ou a raça/cor das mulheres. Os dados provêm da pesquisa Saúde Reprodutiva, Sexualidade e Raça/Cor (SRSR), realizada pelo Cedeplar em 2002. A metodologia baseia-se em curvas de sobrevivência, obtidas pelo estimador de Kaplan-Meier e comparadas através do teste log-rank. Comparing the Ages at First Intercourse, First Union and First Childbirth of Two Cohorts of White and Mixed-race Females in Belo Horizonte, Brazil: Quantitative Indications This paper investigates the ages at first sexual intercourse, first marriage and first childbirth of white and mixed-race (black + brown) females, in the age groups of 20 to 29 and 50 to 59, in the city of Belo Horizonte, Brazil, in 2002. The objectives are twofold. The first aim is to verify the changes in the age at first sexual intercourse, first marriage and first childbirth. The second is to investigate the role of birth cohort and ethnic group /skin color in the differences seen. The data was taken from the survey entitled "Reproductive Health, Sexuality and Color/Ethnic Group [Saúde Reprodutiva, Sexualidade e Raça/Cor]" (SRSR), conducted by Cedeplar in 2002. The methodology is based on survival curves, obtained by Kaplan-Meier estimates, and compared by log-rank tests.